2011
DOI: 10.1590/s0037-86822011000500013
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution and in vitro fluconazole susceptibility of clinical Candida isolates in a Brazilian tertiary-care hospital over a 3-year period

Abstract: Non-albicans Candida species were more frequently isolated in the hospital. Fluconazole resistance was a rare finding in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
5
17
0
Order By: Relevance
“…The latter compound is a triazole frequently prescribed to treat Candida spp. infections because of its excellent patient tolerance and minimal side effects 11 , although a number of species of Candida display fl uconazole resistance 12,13 and the growing worldwide use of this drug to treat candidemia is one of the principal causes of the recent increase in the prevalence of NCAC species 14 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter compound is a triazole frequently prescribed to treat Candida spp. infections because of its excellent patient tolerance and minimal side effects 11 , although a number of species of Candida display fl uconazole resistance 12,13 and the growing worldwide use of this drug to treat candidemia is one of the principal causes of the recent increase in the prevalence of NCAC species 14 .…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to other recent studies conducted in central-western Brazil. Yamamoto et al 20 reported a prevalence of C. albicans of 39% among isolates in Cuiabá, State of Mato Grosso, and other reports from the same country have indicated a predominance of NCAC species over C. albicans in clinical samples isolated from hospitalized patients 12,24 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The most common causative agent is still C. albicans, but its incidence is declining and the frequencies of other species are increasing. Recently, Furlaneto et al 1 noted that non-albicans Candida was the predominant species in different clinical specimens, with the exception of urine samples, in a Brazilian tertiary-care hospital. Invasive candidiasis has a mortality rate that approaches 40% 2,3 .…”
mentioning
confidence: 99%
“…Candida glabrata shows less susceptibility than other Candida species, and the development of resistance to fl uconazole among the clinical strains of C. albicans, C. parapsilosis and Candida tropicalis, hampers the treatment of these infections 13 . The activity against C. neoformans is of particular importance, as this yeast is the major cause of meningitis in AIDS patients and has been identifi ed as the fourth most common cause of life-threatening infection in AIDS patients 14 .…”
Section: Candida Krusei Candida Parapsilosis Candida Tropicalis Cryptmentioning
confidence: 99%